Thermal strain and fluid balance during a 72-km military route march in a field setting - Beng Hoong Poon; Suriya Prakaash; Ya Shi Teo; Priscilla Weiping Fan; Jason Kai Wei Lee (Singapore Medical Journal)
Introduction: A physiological profiling study was conducted to evaluate thermal strain as well as fluid and electrolyte balances on heat-acclimatised men performing a 72-km route march in a field setting. Methods: 38 male soldiers (age range 18–23 years) participated in the study, as part of a cohort that marched for 72 km, with loads for about 26 hours. Core temperature and heart rate sensors were used for the duration of the march. Fluid and food intake and output were monitored for the duration of the march. Blood samples were taken one day before the march (pre-march), immediately after the march (Post 1) and on the 15th day after the march to ascertain recovery (Post 2) to assess fluid and electrolyte profiles. Results: Mean core temperature was within safe limits, ranging from 37.1 to 38.1°C throughout the march. There was an overall decrease in serum sodium levels, a decline in serum sodium concentration in 28 participants and three instances of hyponatraemia (serum sodium concentration <135 mmol/L). Conclusion: Our study found low thermal strain heat-acclimatised individuals during a 72-km route march. However, there was an overall decrease in serum sodium levels, even when the participants were allowed to drink ad libitum. Challenges of exercise-associated hyponatraemia during prolonged activities remain to be addressed.